Commons management and ecotourism: ethnographic evidence from the Amazon. Issue 1 (18th February 2010) - Stronza, Amanda Lee
The paper evaluates the relationship between ecotourism and commons management. Social and economic impacts of ecotourism in an indigenous village in the Peruvian Amazon are considered in relation to opportunities for collective action to manage common pool resources, including wildlife, forests, and river habitats. Longitudinal, ethnographic data gathered over 12 years about a joint venture ecotourism project between a private company and a local community show three outcomes that support commons management and three outcomes that challenge it. The outcomes in favor of commons management include: direct economic returns that act as conservation incentives, strengthened organization resulting from participatory management of ecotourism, and expanded networks of support from outside actors. Outcomes that are challenging the potential for collective action include: direct economic returns that enable expanded individual production and extraction, a new spirit of individual entrepreneurship that threatens to debilitate traditional social relations and institutions, and a conservation ethic that fosters dualistic thinking about people and nature and the zoning of places where resources are used vs. where they are preserved.